Azathioprine plus corticosteroid treatment in Chinese patients with neuromyelitis optica. Issue 7 (July 2015) - Qiu, Wei; Kermode, Allan G.; Li, Rui; Dai, Yongqiang; Wang, Yuge; Wang, Jingqi; Zhong, Xiaonan; Li, Caixia; Lu, Zhengqi; Hu, Xueqiang
Abstract We investigated the efficacy of azathioprine (AZA) plus long-term low dose corticosteroids in Chinese patients with neuromyelitis optica (NMO) and neuromyelitis optica spectrum disorders (NMOSD) at the Center for Demyelinating Diseases, South China. We prospectively enrolled patients between June 2010 and June 2014. Annualized relapse rate (ARR), expanded disability status scale (EDSS) score and modified Rankin Scale (mRS) were analyzed retrospectively. Of 77 patients with NMO/NMOSD (four males, 73 females; age range: 4–69 years), median disease duration before initiation of AZA was 32.0 months (range: 2.0–197.0). Median post-treatment follow-up was 23 months (range: 6–58) and 44 patients (57.1%) were relapse-free at median follow-up 19 months (range: 6–51). Pre-treatment ARR was 0.923, and post-treatment ARR was 0 (p < 0.0001). Survival analysis indicated a significantly lower risk of relapse (hazard ratio 0.522; 95% confidence interval 0.377–0.722; p < 0.0001). Significant improvements were shown in the EDSS (3.0 versus 1.0; p < 0.0001) and mRS (2.0 versus 1.0; p < 0.0001). Our study provides evidence supporting the use of AZA plus a low dose corticosteroid as an effective and safe strategy which is associated with a reduction in the risk of relapse in Chinese patients with NMO.